Evaluation of Renal Venous Impedance, Pyelocalyectasis and Their Correlation during Pregnancy Using Doppler Ultrasound Examination: A Case Control Study - Sharma, P; Shrestha, B; Ansari, MA; Singh, D; Singh, BP (Nepalese Journal of Radiology, 2012)
Objective: The objective of our study was to evaluate venous impedance, pyelocalyectasis and their correlation during pregnancy using Doppler ultrasound examination. Materials and methods: Doppler studies of bilateral kidneys were done in 41 singleton pregnant ladies of second and third trimester of pregnancy and 35 healthy volunteers. None of the ladies had prior history of renal diseases or renal surgery in the past and were clinically asymptomatic. Pelvicalyceal system dilatation of both kidneys was graded based on the separation of sinus echo at mid polar region. Doppler sonography of the interlobar veins of both kidneys was performed at mid polar region and venous impedance index was calculated. Correlation between venous impedance index and hydronephrosis was done using SPSS (11) software. Results: The venous waveforms in pregnant women showed diminished phasic oscillations. Venous impedance in case was 0.31±0.06 on the right side and 0.35±0.09 on the left side and in control group was 0.43±0.06 and 0.40±0.05 on the right and left respectively. Difference between case and control was statistically significant (p < 0.001). During second trimester venous impedance index was 0.34±0.06 and 0.35±0.07 on right and left side respectively. In the third trimester it was 0.31±0.05 on the right side and 0.34±0.10 on the left side. There was negative correlation between venous impedance and grade of hydronephrosis or gestational age. Conclusion: Venous impedance index was significantly lower in pregnant ladies than in control and there was a negative correlation between grades of hydronephrosis and venous impedance index. NJR I VOL 2 I ISSUE 1 25-30 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6976